Evaluating the Current Green Supply Chain Practices Employed by Non-Governmental Organizations in Kenya - Antoney Omondi, Ochieng; Mark, Okowa; Micheni, Elyjoy Muthoni (EuroEconomica, 2025)
Environmental sustainability has become a key concern for global and developing-world non-governmental organizations (NGOs). This study examined the impact of green procurement practices on environmental sustainability among NGOs in Migori County, Kenya. Green procurement involves integrating environmental considerations into purchasing decisions and supplier evaluations to mitigate ecological degradation. A descriptive survey design was used, targeting procurement and operations staff in selected NGOs. Data were collected using structured questionnaires and analysed statistically, with findings supported by inferential analysis. Results indicated a strong, statistically significant relationship between green procurement practices and environmental sustainability. Key organizational practices such as sustainable sourcing, environmental supplier assessments, and preference for recyclable materials contributed to better resource management and reduced environmental impact. The study identified green procurement as the most influential factor in promoting sustainability due to its strategic role within organizations. The findings highlight the need for NGOs to embed environmental criteria in procurement policies and to invest in training programs for procurement staff. This research contributes to the growing body of literature on green supply chain management by emphasizing procurement as a central component in advancing sustainable practices. It offers practical guidelines for enhancing green supply chain initiatives among NGOs in Migori County.